BOARD NETWORKS, DIVERSITY, AND ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Bahaudin, Mohd Fahmee; Jamaludin, Mohd Faizal; Marzuki, Marziana Madah; Zakaria, Nor Balkish (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
This systematic literature review examines how board network centrality and board diversity shape environmental, social, and governance (ESG) performance within corporate governance. Although prior studies have linked director networks and board composition to sustainability-related outcomes, the evidence remains fragmented because these governance attributes are often examined separately. This review addresses that gap by integrating insights from social network and resource dependence perspectives to explain how board connectedness and diversity jointly influence ESG performance, sustainability disclosure, and governance-related innovation. Guided by the PRISMA 2020 framework, the review systematically searched Scopus and Web of Science for English-language journal articles published between 2022 and 2025. After applying explicit inclusion and exclusion criteria, 24 eligible studies were retained and analysed using thematic synthesis. Three dominant themes emerged: (i) board network centrality and governance effectiveness, (ii) board diversity and ESG performance, and (iii) sustainability-driven innovation and reporting practices. The findings indicate that centrally positioned boards are frequently associated with stronger ESG performance, more credible sustainability disclosure, and greater adaptive capacity, particularly in resource-intensive and highly regulated settings. Board diversity, especially gender diversity, generally strengthens transparency, stakeholder responsiveness, and sustainability oversight, although its effects remain contingent on board processes, organisational culture, and institutional context. Overall, this review contributes by offering an integrated governance lens on board networks, diversity, and ESG, while clarifying the organisational and institutional conditions under which board attributes are most likely to support credible and sustained sustainability outcomes.